Evaluation of the company's personnel - Zhang Xinfeng (Kharkiv : V. N. Karazin Kharkiv national university, 2024)
The object of research is Huawei company. The subject of research is the evaluation and optimization of personnel management systems to align with corporate strategic goals. The purpose of the master's thesis is to comprehensively analyze Huawei's personnel management system and provide scientific and practical recommendations to improve its effectiveness. This includes addressing current challenges, integrating innovative tools and methods, and ensuring alignment with Huawei's strategic goals to enhance employee performance, satisfaction, and overall organizational competitiveness in the global market. The research outcomes include a detailed assessment of Huawei's current personnel evaluation practices, identifying strengths and weaknesses, and proposing actionable improvements. This leads to the development of theoretical and practical principles designed to address gaps in the existing system, ensure better alignment with organizational goals, and leverage innovative approaches to personnel evaluation. The obtained results provide valuable insights into the effective evaluation of employees, offering a structured framework and specific recommendations to enhance Huawei's personnel management.
Scientific advisor: Semenchenko T., PhD in education, associate professor, department management, business and professional communications
Keywords: SOCIAL SCIENCES::Social sciences; management; company personnel; methods of personnel evaluation; methods of personnel evaluation; evaluation of personal qualities; evaluation of labor results